Pengaruh Current Ratio, Return on Equity, Debt to Equity Ratio dan Earning per Share terhadap Return Saham - Riska Apriyanti; Tita Safitriawati; Yosi Safri Yetmi (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to examine in depth the influence of financial variables consisting of Current Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning per Share (EPS) on Stock Returns in primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. This study uses a quantitative approach by utilizing secondary data in the form of annual reports published through the official websites of each company and the Indonesia Stock Exchange page, so that the data used can be accounted for its validity. Sample selection was carried out through a purposive sampling technique with certain criteria resulting in 15 sample companies with a total of 75 observation data which were then analyzed using Eviews 13 statistical software. The analysis focused on partial and simultaneous relationships between variables to determine how much each factor contributed to the movement of Stock Returns. The results showed that the Current Ratio had no significant effect on Stock Returns with a probability value of 0.4079, so that company liquidity in the short term was not a major determining factor for investors. Return on Equity also did not show a significant effect with a probability value of 0.2591, indicating that the company's efficiency in generating profits from shareholder equity has not been a consistent benchmark for investment returns. Conversely, the Debt to Equity Ratio was shown to have a significant negative effect on Stock Returns with a probability value of 0.0053, meaning that the higher the company's leverage level, the greater the risk borne, thus implying a decrease in investor interest and a decrease in returns. Earnings per Share also did not have a significant effect on Stock Returns with a probability value of 0.2989, indicating that although EPS is one of the fundamental indicators, in the context of this research period its effect was inconsistent on the returns received.